THE ALGERIAN NOVEL WRITTEN IN FRENCH IN REALISM AND COMMITMENT - ABBOUD, OURIDA ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2019)
This paper deals with the Algerian novel written in French, which appeared as a reaction to some French writters who wanted to falsify the reality of the situation in Algeria during the French colonial period. Through a narrative speech written in the language of the coloniser himself; the Algerian novelist managed to expose the truth of colonial France and to reveal the falsehood of some of its writters alegations. The Algerian novel thus became a vaste space to convey of the algerians suffrings during this period of his history. This litterary experience has permeted to the Algerian novel to enter in to the ranck of world literature.